"Bitwa wołoska" Krzysztofa Poradowskiego – zmagania mołdawskie Samuela Koreckiego i Michała Wiśniowieckiego oraz klęska książąt pod Sasowym Rogiem w roku 1616 - Kuran, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
Nowadays Krzysztof Poradowski is an unknown author. His text Wołoska Battle combines certain plots: occasional, political, and funeral.First part of this text is an appeal to the sons of Kingdom. Author invites young people to participation in the war. What is more, this part notifies about the death of Prince Michal Wiśniowiecki and Samuel Korecki. Poradowski laments and praises for deceased.Second part of the Wołoska Battle is a history of a struggle in the Moldavia and relations after defeat under Saxon Horn in 1616 year. This time Turks caught Samuel Korecki and closed him in the prison.In the third part Poradowski prays to God for liberation and appeals to the knights or war enthusiasm.The last part of the Wołoska Battle is a Latin poetry in form of echo. It’s a next praise of Korecki.